Experimental evidence and network pharmacology identify the molecular targets of Tong Sheng tablets in cerebral ischemia reperfusion injury - Liu, Tuo (Am J Transl Res, 2019)
Purpose: Tong Sheng tablets (TSTs) have long been used for treating cerebral ischemic reperfusion injury (CIRI) in clinic, but the underlying mechanism remains unknown. Therefore, in this study, TSTs were evaluated systematically using chemical analysis, network pharmacology and classical pharmacology. Methods: The first part was TSTs quality control including TSTs fingerprint establishment and chemicals identification. In the second part, network pharmacology analysis and bioinformatics were combined to construct a compound-target-disease network, which can screen out key targets or pathways, revealing complex molecule mechanism of TSTs. The last part was experiment verification. Classical pharmacology of TSTs was investigated in vivo to verify the results of network pharmacology. Results: (1) Fingerprints of TSTs were established, and 11 characteristic peaks were identified using HPLC. (2) Network pharmacology and bioinformatics suggested that the protection of TSTs in treating CIRI might be related to regulation of oxidative stress, inflammation and apoptosis, and some key molecules such as Nrf2, IL-1β, TNF, Bcl-2 and Cyt-C involved in the pathways. (3) TSTs significantly improved neurologic behavior scores, decreased the areas of ischemic necrosis and neuronal necrosis, and increased Nissl body counts. Besides, TSTs significantly decreased pro-inflammatory cytokine (IL-1β, TNF-α) and pro-oxidative product levels (LPO, MDA) and increased anti-oxidative product levels (NO, SOD). TSTs downregulated the protein expressions of Nrf2 and HO-1. Meanwhile, TSTs reduced apoptotic cell counts, downregulated the protein expressions of Cyt-C and Bax, and upregulated the protein expression of Bcl-2. In terms of autophagy, TSTs enhanced LC-3B protein expression. Conclusion: The present results illustrated that TSTs effectively alleviated CIRI, and the underlying mechanism might be associated with multiple molecular pathways. Herein, we established a primary pattern for studying Chinese herbal compounds and provided basic guidance for future investigation.